Effects of SVEP1 on Lung Squamous Cell Carcinoma and its Association with Tumor Mutation Burden, Prognosis, and Immune Regulation - Luo, Yu; Zhang, Min; Wang, Zhibo; Li, Zhihua; Chen, Xiru; Cao, Juan; Que, Jun; Chen, Liang; Deng, Xiaheng (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: The mutated genes in lung squamous cell carcinoma were investigated for their possible association with tumor mutation burden, microsatellite instability, and cancer prognosis. Objective: Our study aims to evaluate the value of the candidate genes as a potential biomarker of lung squamous cell carcinoma and pan-cancer analysis. Methods: The landscape of the tumor microenvironment and infiltrating lymphocytes in lung squamous cell carcinoma was calculated using ESTIMATE and CIBERSORT algorithm. Weighed gene co-expression network analysis was used to screen key modules related to immune cell infiltration. Somatic mutations were found by data analysis from the TCGA and ICGC databases. Mann-Whitney U test was used to evaluate the tumor mutation burden difference between patients with mutant and wild-type SVEP1 genes. The Kaplan-Meier method was used to examine the prognosis of the patients with mutations. The effects of SVEP1 expression on tumor mutation burden and immunity in different cancers were determined by pan-cancer analysis. Results: SVEP1 mutation was found to be associated with a higher tumor mutation burden and prognosis. SVEP1 mutation might be involved in the possible biological process of the anti-tumor immune response. SVEP1 is related to different degrees of immune infiltration in cancer. Moreover, the miRNA-SVEP1 targeting network was used to illuminate the possible mechanisms. Conclusion: SVEP1 mutation and its mRNA expression are related to tumor mutation burden and cancer immunity in lung squamous cell carcinoma. Our findings reveal the underlying mechanisms, indicating that SVEP1 may be a prognostic marker of lung squamous cell carcinoma.
Keywords: tumor immune infiltration